How do you factor ##36x^2 – 25##?

Use the difference of squares identity to find:

##36x^2-25 = (6x-5)(6x+5)##

The difference of squares identity can be written:

##a^2-b^2 = (a-b)(a+b)##

In the case of ##36x^2 – 25##, notice that ##36x^2 = (6x)^2## and ##25 = 5^2##, so we get:

##36x^2-25 = (6x)^2-5^2 = (6x-5)(6x+5)##

Posted in Uncategorized

Leave a Reply

Your email address will not be published. Required fields are marked *

You may use these HTML tags and attributes:

<a href="" title=""> <abbr title=""> <acronym title=""> <b> <blockquote cite=""> <cite> <code> <del datetime=""> <em> <i> <q cite=""> <s> <strike> <strong>